2021
DOI: 10.1002/jssc.202100173
|View full text |Cite
|
Sign up to set email alerts
|

Target profiling of beer styles by their iso‐α‐acid and phenolic content using liquid chromatography–quadrupole time‐of‐flight–mass spectrometry

Abstract: Beer styles show wide variation in color, flavor, and clarity, due to differences in their chemical content. Some of the major flavor compounds in beer are isomerized alpha acids and phenolic compounds. These were investigated as potentially discerning features between beer styles. A selection of 32 American beers covering five styles was analyzed using liquid chromatography quadrupole time-offlight mass spectrometry, which resulted in high mass accuracy chromatograms of the studied analytes. Distinctions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Furthermore, our method, through direct injection without any sample pretreatment, even if utilizing a less sensitive technique compared to LC-MS/MS [41][42][43][44], ensured excellent results in terms of analytical instrument performance. Anderson et al [32], for instance, reported the target profiling of beer styles by IAAs and phenolic compounds using LC-QTOF showing a LOQ (0.33 to 16.5 mg/L) and LOD (0.1 to 3 mg/L) higher than our method and only for ten compounds. Cortese et al [43] provided an accurate and comprehensive quantification of phenolic compounds in craft beers showing LOD and LOQ values similar to our method, but they considered only 20 phenolic compounds utilizing a complex sample pretreatment and extraction procedure as Cheiran et al [44] that, through a HPLC-ESI-MS/MS, found 57 phenolic compounds in craft beers.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Furthermore, our method, through direct injection without any sample pretreatment, even if utilizing a less sensitive technique compared to LC-MS/MS [41][42][43][44], ensured excellent results in terms of analytical instrument performance. Anderson et al [32], for instance, reported the target profiling of beer styles by IAAs and phenolic compounds using LC-QTOF showing a LOQ (0.33 to 16.5 mg/L) and LOD (0.1 to 3 mg/L) higher than our method and only for ten compounds. Cortese et al [43] provided an accurate and comprehensive quantification of phenolic compounds in craft beers showing LOD and LOQ values similar to our method, but they considered only 20 phenolic compounds utilizing a complex sample pretreatment and extraction procedure as Cheiran et al [44] that, through a HPLC-ESI-MS/MS, found 57 phenolic compounds in craft beers.…”
Section: Discussioncontrasting
confidence: 52%
“…CBS2 also showcased a heightened concentration of chlorogenic acid compared to other beers, suspected to have originated from the distinctive brewing ingredients. Significantly, previous studies have identified chlorogenic acid as a major phenolic acid present in oranges and other citrus fruits [32]. Total phenols and bitter units were also determined for these beers, being integral components of the broader quality control processes in the brewing industry aimed at maintaining consistency in taste and characteristics.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Beer styles show wide variation in color, flavor, and clarity, the major flavor compounds are isomerized alpha acids and phenolic compounds [219]. First, the polyphenols mechanism (phenolic acids, flavonoids) of beer in preventing and treating 22 human chronic diseases is the interaction between polyphenols of barley grains and flavonoids of barley malt and hops; Flavonoids especially saponarin and lutonarin in barley grass have similar 11 health effects [221]. Second, the melatonin mechanism of beer in preventing and treating 14 human chronic diseases is the interaction between melatonin and GABA as well as tryptophan of barley malt; In the body, melatonin is synthesized from a tryptophan by leading to competitive O-demethylation and C6-aromatic hydroxylation pathways [222]; Tryptophan in barley grass have similar 4 health effects [219].…”
Section: Active Peptides Mechanismmentioning
confidence: 99%
“…Additionally, typical issues of reproducibility, ruggedness, and limited understanding of the retention mechanism in HILIC mode were still not fully overcome [12,20,21] and most studies used elaborated tandem-MS instruments [20,22,23]. Beer samples were selected as an exemplary matrix due to their complexity consisting of organic solvent and water, various fermentation products, polymeric as well as small molecules, and the availability of extensive comparison studies in the context of metabolomics and AA analysis [24][25][26][27][28][29][30]. Significant matrix effects in beer samples and differences between RPLC and HILIC mode were found for the analysis of biogenic amines which are structurally similar in comparison to AAs [31].…”
Section: Introductionmentioning
confidence: 99%